Neuroprotective effect of Centella asiatica (L.) Urb. against toxicity induced by different neurotoxic agents in neuroblastoma SH-SY5Y cells / Heymmela Kasi - Heymmela , Kasi (2019)
Neurodegenerative diseases are characterized by the progressive dysfunction and death of neuronal cells and oxidative stress has been identified as one of the major cause of a range of neurodegenerative disorders. Most of the current therapies of neurodegenerative diseases involve usage of synthetic drugs which are believed to have some inadequacies. Thus, there has been a great interest towards using plant derived natural products as a potential neuroprotective agent. The present study aimed to investigate the neuroprotective effects of methanolic and water extracts of Centella asiatica against neurotoxic agents (hydrogen peroxide (H2O2) and acrylamide)-induced toxicity in human neuroblastoma SH-SY5Y cells. Prior to the neuroprotective assay, a preliminary screening was conducted to assess the toxicity of dimethyl sulfoxide (DMSO), neurotoxic agents and extracts of C. asiatica towards SH-SY5Y cells. The results demonstrated that DMSO and both extracts had no significant toxicity effect towards the cells at concentration range of 0.05 to 1.25% (v/v) and 1 to 100 μg/ml, respectively. The half-maximal inhibitory concentration (IC50) of H2O2 and acrylamide was found to be 100 μM and 5 mM, respectively and these concentrations were used to induce toxicity in the cells during neuroprotective assays. The neuroprotective effect was assessed through cell viability using MTT assay whereby the cells were pre-treated with extracts of C. asiatica and then exposed to H2O2 and acrylamide separately. The results revealed that both methanolic and water extracts exhibited a mild neuroprotective activity against H2O2 and acrylamide-induced toxicity in SH-SY5Y cells. The neuroprotective activity of methanolic extract was observed to be higher than water extract and both extracts conferred a better neuroprotection towards the cells against toxicity caused by H2O2 than acrylamide. In addition, the combined neuroprotective effects of extracts of C. asiatica and curcumin against H2O2 and acrylamide-induced toxicity in the cells was also investigated. Before that, the neuroprotective potential of curcumin against the neurotoxic agents-induced toxicity was investigated. The results revealed that curcumin had a considerable neuroprotective effect against both neurotoxic agents. For combination study, the results indicated that the combination of the extracts with curcumin slightly improved the neuroprotective activity against toxicity-induced by H2O2 while no improvement was observed in the neuroprotection against toxicity-induced by acrylamide. Besides that, antioxidant activity of curcumin and extracts of C. asiatica was determined through in vitro antioxidant assays such as DPPH radical scavenging assay, ABTS radical scavenging assay and iron chelating assay. The results showed that curcumin had an effective DPPH and ABTS radical scavenging activity than methanolic and water extracts. Among the extracts, water extract exhibited a slightly higher antioxidant activity compared to methanolic extract. The iron chelating activity of curcumin and methanolic extract was not able to be determined. In conclusion, methanolic extract of C. asiatica is a potential neuroprotectant and both the extracts and its combination with curcumin demonstrated a better neuroprotective activity against toxicity-induced by H2O2 compared to acrylamide. The mild neuroprotective effects of extracts of C. asiatica and its combination with curcumin might be due to the moderate antioxidant activity of the extracts. Further recommendations for future study were also suggested in this study.